EVALUASI DISIPLIN KERJA PADA PUSDIK BINMAS LEMDIKLAT POLRI - Putra Ari Wijayanto; Muhammad Suud; Suci Utami Wikaningtyas (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2021)
The objectives of this study are: 1) To identify the factors that cause indiscipline at the Pusdik Binmas Lemdiklat Polri. 2) To analyze why the discipline at the Pusdik Binmas Lemdiklat Polri is not optimal. 3) To identify how the work discipline is at the Pusdik Binmas Lemdiklat Polri. 4) To formulate efforts to improve work discipline at the Pusdik Binmas Lemdiklat Polri. This research is more appropriate to use a qualitative approach. The results showed that the work discipline of police officers would affect their performance in serving the community. Pusdik Binmas Lemdiklat Polri has carried out its duties as well as possible, this of course cannot be separated from the participation and support of the leadership who always provides guidance, direction and instructions in carrying out their duties, so that every member of the Head of Education and Training Center for the National Education and Training Center of the Police tries to provide the best service to the community . As the specific conclusions of this study, as follows: The desired work discipline in improving services to the community; The form of work discipline, and its application. Desired discipline and ways of socializing it; Implementation of Work Discipline; Evaluation of Work Discipline; and follow-up work discipline.